The Wiley-Blackwell companion to political sociology - Amenta, Edwin, 1957-; Nash, Kate, 1958-; Scott, Alan, 1956- (Hoboken, NJ : John Wiley & Sons, 2012)
The Wile-Blackwell Companion to Political Sociology is a complete reference guide, reflecting the scope and quality of the discipline, and highlighting emerging topics in the field. Global in focus, offering up-to-date topics from an interdisciplinary, international set of scholars addressing key issues concering globalization, social movements, and citizenship. The majority of chapters are new, including those on environmental politics, international terrorism, security, corruption, and human rights. Revises and updates all previously published chapters to include new themes and topics in.
B. Structures of Participation39 Towards a Political Sociology of Human Rights; 40 Democratization; 41 Feminism and Democracy; 42 Democracy and Capitalism in the Wake of the Financial Crisis; References; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Political sociology; Aufsatzsammlung; Political sociology; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Political sociology; Politisk sociologi; Electronic books